ANALYSIS OF GRAMMATICAL COHESION TOOLS IN STUDENTS ESSAY AT INDRAPRASTA PGRI UNIVERSITY - Reni Rokhayati; Ila Nafilah; Arinah Fransori (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Abstract: The purpose of this study is to analyze and describe or obtain a clear picture of grammatical cohesion consisting of references, substitutions, ellipsis, and conjunctions in the essays of Indraprasta PGRI University students. This study used descriptive qualitative method. In this study the fact of language is in the form of discourses in essays with a focus on the study of grammatical cohesion analysis. The methode used in this researched  inquired methode with notes-taken technique, which mean the researcher recorded the data that was considered appropriate in the study of cohesion analysis and discourse coherence in student essays. The technique used is to analyze based on one-to-one relationships with other sentences in the essay. The data source used is a student essay in the Literature Psychology course, there are 30 student essays taken as research data. The results of this study indicate that the grammatical cohesile device is; reference 46 with a percentage of 24.1%, substitution 5 with a percentage of 2.6%, ellipsis 8 with a percentage of 4.2% and conjunctive relations 132 with a percentage of 69.1%. Based on this, from 30 essays written by students there are 191 numbers of grammatical cohesion tools used.Key Words: student essay, tool for grammatical cohesion, conjungsion